Experimental design modelling for the extraction of vanadium(IV) extraction V(IV)-SO4 2- (H+, Na+)-Cyanex 301-kerosene system - Karmakar, AK; Biswas, RK (Bangladesh Journal of Scientific and Industrial Research, 2021)
The vanadium(IV) extraction from acidic sulphate medium by Cyanex 301 (bis-(2,4,4-trimethylpentyl) dithiophosphinic acid) dissolved in kerosene is explored from the modelling point of view. The time of equilibration is only 10 min and above pH(eq) = 2, high extraction (>90%) occurs.On keeping organic to aqueous phase ratio of 1, factors affecting the extent of extraction (log D and log CD) are pH(eq), [V(IV)],[SO4 2-], [Cyanex 301]and temperature (T). The high (+) and low (-) levels are considered for the factors. The 25 factorial design is used to find the regression equation for the V(IV) extraction by Cyanex 301. On symbolizing pH(eq), log [V(IV)], , log [SO4 2-], log [Cyanex 301], and 1/T (K-1); where concentration terms are in mol/L, as P , M, S,E, and (1/T), respectively,the regression equation obtained is: log CD = 1.95 - 0.23 M + 1.83 P + 2.07 E + 0.84 S - (888.9/T) - 0.26 PS.The current system shows only the interaction effect among pH(eq) and [SO4 2-]. The equation can well describe the system,and it can be used to optimize factors for satisfactory extraction. Bangladesh J. Sci. Ind. Res.56(2), 95-104, 2021